Cellular distribution of PACAP-38 and PACAP receptors in the rat brain: Relation to migraine activated regions. (May 2020) - Warfvinge, Karin; Edvinsson, Lars
Background: Pituitary adenylate cyclase-activating polypeptide (PACAP) occurs as either a 27- or 38-amino acid neuropeptide and belongs to the vasoactive intestinal polypeptide/glucagon/secretin family of peptides. PACAP and vasoactive intestinal polypeptide have a 68% homology of their amino acid sequences and share three B-type G-protein coupled receptors: VPAC1, VPAC2 and PAC1 receptors. Methods/results: The distribution of PACAP-38 and its receptors in the brain is only partly described in the literature. Here, we have performed a study to provide the more general picture of this system in rat brain in order to understand a putative role in primary headaches and partly in relation to the calcitonin gene-related peptide system. We observed a rich expression of PACAP-38 and PAC1 receptor immunoreactivity in many regions throughout the cerebrum, cerebellum and brainstem. The expression pattern points to multiple functions, not least associated with pain and reactions to pain. The expression of VPAC1 and VPAC2 receptor immunoreactivity was very sparse. In several regions such as the cerebral cortex, trigeminal nucleus caudalis, hypothalamus and pons there was a close relation to calcitonin gene-related peptide expression. Conclusion: The findings suggest that the rich supply of PACAP-38 and PAC1 receptors is associated with basic functional responses in the central nervous system (CNS), and there are important close anatomical relations with calcitonin gene-related peptide in CNS regions associated with migraine pathophysiology.